Monitoring Tumor Targeting and Treatment Effects of IRDye 800CW and GX1-Conjugated Polylactic Acid Nanoparticles Encapsulating Endostar on Glioma by Optical Molecular Imaging - Yaqian Li; Yang Du; Xia Liu; Qian Zhang; Lijia Jing; Xiaolong Liang; Chongwei Chi; Zhifei Dai; Jie Tian (Molecular Imaging, 2015)
Molecular imaging used in cancer diagnosis and therapeutic response monitoring is important for glioblastoma (GBM) research. Antiangiogenic therapy currently is one of the emerging approaches for GBM treatment. In this study, a multifunctional nanoparticle was fabricated that can facilitate the fluorescence imaging of tumor and deliver a therapeutic agent to the tumor region in vivo and therefore possesses broad application in cancer diagnosis and treatment. This particle was polylactic acid (PLA) nanoparticles encapsulating Endostar, which was further conjugated with GX1 peptide and the near-infrared (NIR) dye IRDye 800CW (IGPNE). We demonstrated noninvasive angiogenesis targeting and therapy of IGPNE on U87MG xenografts in vivo using dual-modality optical molecular imaging including NIR fluorescence molecular imaging (FMI) and bioluminescence imaging (BLI). The NIR FMI results demonstrated that IGPNE had more accumulation to the tumor site compared to free IRDye 800CW. To further evaluate the antitumor treatment efficacy of IGPNE, BLI and immunohistochemistry analysis were performed on tumor-bearing mice. With the aid of molecular imaging, the results confirmed that IGPNE enhanced antitumor treatment efficacy compared to free Endostar. In conclusion, IGPNE realizes real-time imaging of U87MG tumors and improves the antiangiogenic therapeutic efficacy in vivo.